ANALISA ALGORITMA K-MEANS CLUSTERING PEMETAAN JUMLAH TINDAK PIDANA - Jajang jaya Purnama (Lambung Mangkurat University, 2019)
Marine fisheries is an effort to catch marine fish, fishermen catch fish in the sea using two kinds of ways, namely through traditional and modern methods. to support the daily lives of fishermen looking for sea fish. the abundance of marine fish in the Indonesian sea means that the processed food is also very diverse. The high level of crime in the Indonesian sea is a mirror of the quality of the Indonesian navy's military defense, considering that the Indonesian sea is very rich in marine resources which makes fish thieves from neighboring countries tempted to catch fish in the Indonesian sea. in general it can be called a crime if unlicensed fishermen, illegal fishing gear, without permission and illegal fishing gear, falsification of documents, incomplete documents, shocking (ACCU), carrying explosives / bombs, fishing ground, fishing ground and illegal logging equipment , fish transportation / transhipment, without information on criminal types of fisheries, transhipment and fishing gear, no transmitter, theft of coral reefs, unsuitable fishing gear (SIPI), incomplete documents and fishing ground, foreign crew members not suitable for SIPI, not fishing in accordance with SIKPI, documents are incomplete and there are no transmitters, SIB is not valid, SLO (SIB is not in accordance with SIPI), without permits and fake documents, sea sand without documents, do not have SLO, loading and unloading is not SIPI, uses chemical / biological / explosives, fishing in the Gray Area / illegal fishing equipment / returned to the country of origin related to the MoU. Based on the background described there are problems that occur, the formulation of the problem in this study are: Analyzing k-means clustering by using proximity euclidean distance distance, How to group data using K-means clustering for illegal fishing crime into the category of illegal crime fishing the highest, medium, and sufficient cases in 266 data with the euclidean distance calculation.Keywords : criminal act, clustering, k-means Perikanan laut merupakan usaha menangkap ikan laut, para nelayan menangkap ikan di laut menggunakan dua macam cara yaitu melalui cara traditional dan modern. untuk menunjang kehidupan sehari-hari nelayan mencari ikan kelaut. melimpahnya ikan laut di laut Indonesia berarti menjadikan olahan masakannya juga sangat beragam. Tingginya tingkat kejahatan di laut Indonesia merupakan cermin kualitas pertahanan militer angkatan laut Indonesia, mengingat laut Indonesia sangat kaya akan baharinya yang membuat para pencuri ikan dari negara-negara tetangga menjadi tergiur untuk menangkap ikan di laut Indonesia. secara umum bisa disebut tindak kejahatan bila mana nelayan tanpa ijin, alat tangkap terlarang, tanpa ijin dan alat tangkap terlarang, pemalsuan dokumen, dokumen tidak lengkap, penyetruman (ACCU), membawa bahan peledak/bom, fishing ground, fishing ground dan alat tagkap terlarang, pengangkutan ikan/transhipment, tanpa keterangan jenis pidana perikanan, transhipment dan alat tangkap, tidak ada transmitter, pencurian terumbu karang, alat tangkap tidak sesuai ijin (SIPI), dokumen tidak lengkap dan fishing ground, ABK asing tidak sesuai SIPI, menampung ikan tidak sesuai SIKPI, Dokumen tidak lengkap dan tidak ada transmitter, SIB tidak berlaku, SLO (SIB tidak sesuai dengan SIPI), tanpa ijin dan dokumen palsu, pasir laut tanpa dokumen, tidak memiliki SLO, bongkar muat tidak sesuai SIPI, menggunakan bahan kimia/biologis/peledak, penangkapan ikan di daerah Grey Area/alat tangkap terlarang/dikembalikan ke negara asal terkait MoU. Berdasarkan latar belakang yang telah diuraikan terdapat permasalahan yang terjadi, rumusan permasalahan dalam penelitian ini adalah : Menganalisa k-means clustering dengan menggunakan kedekatan jarak euclidean distance, Bagaimana melakukan pengelompokan data menggunakan K-means clustering bagi tindak pidana ilegal fishing kedalam kategori tindak pidana ilegal fishing paling tinggi, menengah, dan cukup.studi kasus pada 266 data dengan perhitungan euclidean distance.Kata Kunci : tindak pidana, clustering, k-means